Implementation of Gender Equality and Culture of Stigma Against Women in the Employment Sector - Marito, Dwi Sihol (Universitas Negeri Semarang, 2023)
The implementation of gender equality in the employment sector remains a significant challenge globally, often hindered by deep-rooted cultural stigma against women. Despite progress in legal frameworks and international conventions advocating for gender equality, women continue to face systemic barriers in accessing equal employment opportunities, fair wages, and career advancement. This paper explores the persistent cultural stigma against women in the workplace and how it undermines efforts to achieve true gender equality. The study examines various forms of discrimination, including biased hiring practices, wage gaps, limited access to leadership roles, and the undervaluation of traditionally